Method for testing lithium content of lithium ion battery

By constructing the relationship between the content of lithium element in hydrogen and aqueous solution, combined with weight calibration, the accuracy of lithium-ion battery measurement is solved, and the evaluation of battery safety and life is achieved.

CN119861295APending Publication Date: 2025-04-22TIANMU LAKE INST OF ADVANCED ENERGY STORAGE TECH CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202311356750.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-19
Publication Date
2025-04-22

AI Technical Summary

Technical Problem

The prior art is difficult to accurately measure the amount of lithium extracted in lithium-ion batteries, resulting in battery safety hazards and shortened service life, and there are errors and uncertainties in conventional methods.

Method used

By constructing the relationship between hydrogen content and lithium content and the relationship between lithium element and lithium content in aqueous solution, combining weights Q1 and Q2, the equation F(XA,XB) of the lithium content in the negative electrode sheet is established to accurately measure the lithium evolution amount.

Benefits of technology

It realizes rapid and accurate measurement of lithium-ion-extraction amount of battery, establishes a relationship matrix such as battery operating conditions - SOC - temperature - lithium-ion-number of cycles, and provides a reference solution for safe use of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004501972410000081
    Figure BDA0004501972410000081
  • Figure FDA0004501972400000021
    Figure FDA0004501972400000021
  • Figure FDA0004501972400000022
    Figure FDA0004501972400000022
Patent Text Reader

Abstract

The invention discloses a method for testing the lithium content of a lithium ion battery. The testing method comprises the following steps: S1, carrying out charge-discharge circulation on the lithium ion battery to be tested; s2, disassembling the lithium ion battery, obtaining a negative pole piece, fully reacting the negative pole piece with water, collecting hydrogen, detecting a lithium element in an aqueous solution, introducing the content of the hydrogen into a relational expression f1 (XA) between the content of the hydrogen and the content of the lithium, and introducing the content of the lithium element in the aqueous solution into a relational expression f2 (XB) between the content of the lithium element and the content of the lithium in the aqueous solution; and S3, substituting the test results of the hydrogen and lithium element contents into an equation F (XA, XB) = Q1f1 (XA) + Q2f2 (XB) to determine the lithium content in the negative pole piece. The method disclosed by the invention can be suitable for testing the lithium content in an unknown battery negative electrode, so that the actual lithium content and the lithium precipitation amount of the battery can be obtained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of battery detection, and in particular to a method for testing the lithium content of a lithium ion battery. Background Art

[0002] As one of the main components for realizing the electrification of China, the safety of lithium-ion batteries during use has always been a hot topic of concern to the majority of users. At present, the conventional negative electrode material in lithium-ion batteries is graphite negative electrode material. The potential of the graphite negative electrode when it is close to the full embedding state is very close to the electroplating potential of lithium metal. Therefore, under some special working conditions such as fast charging / low temperature charging, the negative electrode often has significant lithium precipitation. Although some existing studies have shown that the lithium precipitation on the surface of the graphite negative electrode can be partially re-embedded in the subsequent charge and discharge cycle, there are still some cases where some metallic lithium cannot be eliminated in the later cycle process. Moreover, on the one hand, lithium precipitation will lead to serious lithium loss, causing the battery capacity to decay rapidly and greatly shortening the battery life; on the other hand, if more active metallic lithium accumulates on the surface of the negative electrode, they will further accumulate during the charge and discharge process. In addition, due to the uneven current distribution on the surface of the pole piece, there is a great probability that needle-shaped or dendritic lithium dendrites will be formed. Although the separators of current commercial batteries are coated with a micron-thick ceramic layer on the surface, when lithium dendrites accumulate to a certain extent, needle-shaped and branch-shaped lithium dendrites may still break through the separator and contact the positive electrode, causing serious internal short circuit problems in the battery, thereby triggering thermal runaway of the battery, greatly increasing the safety risks of lithium-ion batteries.

[0003] At present, the main methods for lithium plating detection are: (1) setting specific working conditions and using test curves to judge, such as ICA and DVA tests to judge the lithium plating signal peak; (2) using a high-precision thickness gauge to measure the obvious change in the thickness of soft-pack batteries; (3) using a high-precision charge and discharge cabinet to judge lithium plating based on the difference in coulomb efficiency; and (4) testing the electrochemical impedance spectrum of lithium-ion batteries to reflect the lithium plating phenomenon through abnormal signal steps in the impedance spectrum. However, in the actual test process, it is found that even if there is weak lithium plating after the battery is disassembled, the ICA and DVA curves do not change significantly compared with normal batteries. At the same time, since some methods mainly rely on differential thinking, if the mathematical tools are not handled properly, some non-existent "false peaks" will be generated, resulting in errors in the lithium plating test results. Furthermore, some relatively mature non-destructive lithium plating methods cannot directly obtain the amount of lithium plating on the negative electrode sheet. Therefore, providing an effective method for measuring the amount of lithium plating can provide more accurate information for evaluating the degree of lithium plating under various working conditions of the battery. Summary of the invention

[0004] The present invention aims at solving the problems in the prior art and discloses a method for testing the lithium content of a lithium-ion battery. The method of the present invention can realize quantitative processing of the lithium deposition content of the battery.

[0005] The present invention is achieved through the following technical solutions:

[0006] The present invention provides a method for testing the lithium content of a lithium ion battery, the testing method comprising:

[0007] S1: The lithium-ion battery to be tested is first charged and discharged in cycles;

[0008] S2: Disassemble the lithium-ion battery, obtain the negative electrode plate and fully react with water, collect hydrogen and detect the lithium element in the aqueous solution, and bring the hydrogen content into the relationship between the hydrogen content and the lithium content f1( XA ), the content of lithium in the aqueous solution is brought into the relationship between lithium in the aqueous solution and lithium content f2 ( XB );

[0009] S3: Substitute the test results of hydrogen and lithium content into equation F( XA,XB )=Q1f1( XA )+Q2f2( XB ) to determine the lithium content in the negative electrode sheet, wherein Q1 is the relationship f1( XA ), Q2 is the weight of the relationship f2( XB ) weight, F( XA,XB ) is the relationship between the lithium content in the negative electrode sheet, and the weight Q1 and weight Q2 are obtained by the relationship f1( XA ) and the relation f2( XB ) is weighted by the square of the calibration error between the test value and the theoretical value.

[0010] The above design of the present invention constructs the relationship between hydrogen content and lithium content f1( XA ) and the relationship between lithium element and lithium content in aqueous solution f2( XB ), the two relationships are corrected each other, so as to construct the equation for the lithium content in the negative electrode sheet. The amount of lithium precipitated in the negative electrode sheet can be obtained by the difference between the lithium content result obtained by the test and the lithium insertion amount of the sample at 100% SOC. By simultaneously detecting the hydrogen content and the lithium element in the aqueous solution, the lithium content in the negative electrode sheet can be obtained quickly and accurately.

[0011] As a further solution, the relationship between the hydrogen content and the lithium content is expressed as f1( XA) comprises: selecting lithium metals of different masses and recording them as X1, X2, X3...Xn, placing lithium metals in a glass container, sealing the bottle mouth with a rubber stopper and a sealing cover, injecting deionized water, extracting gas, testing the content of hydrogen in the gas, recording them as XA1, XA2, XA3...XAn, fitting the mass X of lithium metal and the content of hydrogen to obtain the relationship between the content of hydrogen and the content of lithium f1( XA ).

[0012] As a further solution, the number of the lithium metals is not less than 7.

[0013] As a further solution, the mass of the lithium metal is 0.1 mg-1 g.

[0014] As a further solution, the volume of the deionized water is 0.1 mL-1000 mL.

[0015] As a further solution, those skilled in the art can select the volume of the extracted gas according to the sampling requirement of the equipment for testing the hydrogen content.

[0016] As a further solution, the relationship between the lithium element in the aqueous solution and the lithium precipitation is expressed as f2 ( XB ) comprises: selecting lithium metals of different masses and recording them as X1, X2, X3...Xn, placing the lithium metals in a glass container, sealing the bottle mouth with a rubber stopper and a sealing cover, injecting deionized water, filtering, testing the lithium element signal in the solution with an inductively coupled plasma spectrometer, recording them as XB1, XB2, XB3...XBn, fitting the mass X of the lithium metal and the content of the lithium element in the aqueous solution with a function, and obtaining a relationship between the lithium element in the aqueous solution and the lithium content f2( XB ).

[0017] As a further solution, the number of the lithium metals is not less than 7.

[0018] As a further solution, the mass of the lithium metal is 0.1 mg-1 g.

[0019] As a further solution, the volume of the deionized water is 0.1 mL-1000 mL.

[0020] As a further solution, the relationship between the hydrogen content and the lithium content is obtained as f1( XA ), we also need to change the relation f1( XA ) for calibration, the calibration method comprising: selecting lithium metal with a mass of X, placing the lithium metal in a glass container, sealing the bottle mouth with a rubber stopper and a sealing cover, injecting deionized water, extracting gas, testing the hydrogen content XA in the gas, and substituting the test result XA into the relational formula f1( XA) is calculated, and the result value is f1( XA ), and calibrate between the theoretical value X and the test result value to obtain the error value R1.

[0021] As a further solution, the relationship between the lithium element and the lithium content in the aqueous solution is obtained as f2( XB ), we also need to change the relationship f2( XB ) for calibration, the calibration method comprising: selecting lithium metal with a mass of X, placing the lithium metal in a glass container, sealing the bottle mouth with a rubber stopper and a sealing cover, injecting deionized water, filtering, and testing the lithium element signal in the solution with an inductively coupled plasma spectrometer. The test result is XB, and the test result XB is substituted into the relationship f2( XB ) is calculated, and the result is f2( XB ), and calibrate between the theoretical value X and the test result value to obtain the error value R2.

[0022] As a further solution, Q1 is The Q2 is

[0023] As a further solution, the charge-discharge cycle ratio is 0.01C-10C, and the number of charge-discharge cycles is 1-100 times, which can ensure that lithium ion batteries will not produce lithium deposition.

[0024] As a further solution, the battery is charged after the charge and discharge cycle until the SOC is 100%-200%.

[0025] As a further solution, the specific operation of disassembling the lithium-ion battery includes: after disassembling the battery in an environment where the dew point is controlled below -40°C, the battery cell is fully left for 0.5h-1h before disassembling the battery cell.

[0026] As a further solution, the negative electrode plate is dried before the negative electrode plate fully reacts with water.

[0027] As a further solution, the drying temperature is 20°C-120°C, the drying time is 1h-24h, and the vacuum degree of the drying environment is -0.03MPa to -0.005MPa, which can improve the accuracy of lithium precipitation testing.

[0028] As a further solution, the area of ​​the negative electrode plate is controlled at 0.5 cm 2 -100cm 2 .

[0029] The present invention also provides the application of the lithium content testing method of a lithium ion battery in testing the lithium content and lithium precipitation content of a negative electrode of a battery.

[0030] The characteristics and beneficial effects of the present invention are:

[0031] (1) The present invention is highly operable for testing the amount of lithium deposition in batteries. It only needs to match the appropriate initial lithium metal mass range or deionized water volume according to the capacity specifications of different batteries to be applicable to quantitative testing of batteries with different capacities / different lithium deposition states. Through this detection method, a relationship matrix of battery operating conditions-SOC-temperature-lithium deposition amount-cycle number can be effectively established, which provides good help for establishing a reference plan for the safe use of lithium-ion batteries.

[0032] (2) The method of the present invention can be applied to test the lithium content in the unknown negative electrode of the battery, and thus the actual lithium insertion and deposition amount of the battery can be obtained. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0034] Figure 1 The relationship between the hydrogen content and lithium precipitation established in the embodiment of the present invention is f1( XA ).

[0035] Figure 2 The relationship between the lithium element in the aqueous solution and the lithium precipitation is established in the embodiment of the present invention. XB ). DETAILED DESCRIPTION

[0036] In order to facilitate understanding of the lithium content testing method of a lithium ion battery of the present invention, the lithium content testing method of a lithium ion battery of the present invention will be described in more detail below, and embodiments of the present invention are given, but the scope of the present invention is not limited thereby.

[0037] Establish the relationship between hydrogen content and lithium precipitation f1( XA ) and the relationship between lithium element in aqueous solution and lithium precipitation f2( XB ):

[0038] Select 0.37mg, 0.92mg, 1.24mg, 1.95mg, 2.45mg, 3.19mg, and 3.53mg of lithium metal, place them in 50mL sealable glass bottles, inject 10ml of deionized water into the glass bottles with a syringe, stir thoroughly, extract 10mL of gas in the glass bottles with a sealed needle, and pass it into a gas chromatograph for testing to obtain f1( XA)-XA is f1( XA )=(XA+3.6512) / 52.4131, where XA represents the hydrogen peak area measured by gas chromatography equipment. Figure 1 shown.

[0039] The content of lithium ions in the solution was tested by inductively coupled plasma spectrometer, so that f2( XB )-XB is f2( XB )=0.01×XB-1.9418, where XB represents the lithium signal value tested by the inductively coupled particle spectrometer. Figure 2 shown.

[0040] For the relation f1( XA ) and the relation f2( XB ) for calibration:

[0041] Continue to select lithium metal blocks with masses of 1.52 mg, 1.88 mg, and 2.71 mg, respectively, place the electrode in a glass container, seal the bottle mouth with a rubber stopper and a sealing cap, inject deionized water, extract gas, and the hydrogen peak areas in the test gas are 75.343, 99.014, and 143.825, respectively. Substitute the test results into the relationship f1( XA ) were calculated, and the calculated results were 1.51mg, 1.96mg, and 2.81mg, respectively. The difference between the theoretical value and the calculated result was Calibration is performed, where σ represents the standard deviation and n represents the number of tests, and an error value R1=0.043 is obtained.

[0042] The above solution was filtered and the lithium element signal in the solution was tested by inductively coupled plasma spectrometer. The test results were 352.29, 395.11, and 472.84. The test results were substituted into the relational formula f2( XB ) was calculated, and the calculated results were 1.58mg, 2.01mg, and 2.79mg. The theoretical values ​​and the calculated results were compared according to Calibration is performed, where σ represents the standard deviation of the test result, and n represents the number of tests, and an error value R2=0.055 is obtained.

[0043] According to formula Q1, The Q2 is

[0044] Substitute R1 and R2 into the above equation to calculate Q1 and Q2, and obtain the final equation relationship: F( XA,XB )=Q1f1( XA )+Q2f2( XB ).

[0045] Instructions for calculating the amount of lithium precipitation (the calculated mass unit is mg, and the capacity unit is mAh):

[0046] The average capacity of the initial cycle of the battery is regarded as the capacity of the sample at 100% SOC, recorded as C1, and the capacity of the battery when lithium is inserted to different SOC states (such as lithium insertion to 105% SOC in Example 1) is recorded as C2. The "theoretical value" of lithium precipitation is (C2-C1) / 3.86, and the test value of lithium precipitation is

[0047] Embodiment 1:

[0048] The button half-cell has an average capacity of about 5.09 mAh after 3 weeks of charge and discharge cycles at 0.2C constant current. It is discharged (lithium embedded) at 0.2C constant current to 105% SOC (about 5.34 mAh, the actual amount of lithium embedded is about 1.38 mg, and the "theoretical value" of lithium precipitation is about 0.06 mg) and left for 1 hour. The button battery is disassembled, the pole piece is taken out and placed in a 40°C vacuum drying oven (vacuum degree: -0.01 MPa) for 1 hour, the pole piece is put into a dry sealable glass bottle, 10 ml of deionized water is injected, and after fully stirring, there are no obvious bubbles in the glass bottle, filter, collect the remaining liquid, and after fully stirring, use a sealing needle to extract 10 ml of gas in the glass bottle, pass it into a gas chromatography device for testing, and the peak area of ​​H2 is 67.231, and the lithium element value in the solution is tested by an inductively coupled plasma spectrometer to be 340.07, and then brought into F( XA,XB )=Q1f1( XA )+Q2f2( XB ) was calculated and the result was about 1.39 mg, and the calculated lithium precipitation amount was about 0.07 mg.

[0049] Example 2: The button-type half-cell has an average capacity of about 5.31 mAh after 3 weeks of charge and discharge cycles at 0.2C constant current, and is discharged (lithium insertion) at 0.2C constant current to 110% SOC (about 5.84 mAh, the actual amount of lithium insertion is about 1.51 mg, and the "theoretical value" of lithium precipitation is about 0.13 mg). The button-type battery is disassembled, the electrode is taken out and placed in a 40°C vacuum drying oven (vacuum degree: -0.01 MPa) for drying for 1 hour, the electrode is placed in a dry sealable glass bottle, 10 ml of deionized water is injected, and after fully stirring until there are no obvious bubbles in the glass bottle, filter and collect the remaining liquid. After fully stirring, 10 ml of gas is extracted from the glass bottle with a sealing needle, and it is passed into a gas chromatography device for testing to obtain a peak area of ​​H2 of 73.285, and an inductively coupled plasma spectrometer is used to test the lithium element value in the solution to be 354.49, and then F( XA,XB )=Q1f1(XA )+Q2f2( XB ) was calculated and the result was about 1.52 mg, and the calculated lithium precipitation amount was about 0.14 mg.

[0050] Example 3: The button-type half-cell has an average capacity of about 5.43 mAh after 3 weeks of charge and discharge cycles at 0.2C constant current, and is discharged (lithium insertion) at 0.2C constant current to 120% SOC (about 6.52 mAh, the actual amount of lithium insertion is about 1.69 mg, and the "theoretical value" of lithium precipitation is about 0.28 mg). The button-type battery is disassembled, the pole piece is taken out and placed in a 40°C vacuum drying oven (vacuum degree: -0.01 MPa) for drying for 1 hour, the pole piece is put into a dry sealable glass bottle, 10 ml of deionized water is injected, and after fully stirring, there are no obvious bubbles in the glass bottle, filter, collect the remaining liquid, and after fully stirring, use a sealing needle to extract 10 ml of gas in the glass bottle, pass it into a gas chromatography device for testing, and the peak area of ​​H2 is 82.413, and the lithium element value in the solution is tested by an inductively coupled plasma spectrometer device. 374.16, and then brought into F( XA,XB )=Q1f1( XA )+Q2f2( XB ) was calculated and the result was about 1.70 mg, and the calculated lithium precipitation amount was about 0.29 mg.

[0051] Example 4: The button-type half-cell has an average capacity of about 5.23 mAh after 3 weeks of charge and discharge cycles at 0.2C constant current, and is discharged (lithium insertion) at 0.2C constant current to 150% SOC (about 7.85 mAh, the actual amount of lithium insertion is about 2.03 mg, and the "theoretical value" of lithium precipitation is about 0.68 mg). The button-type battery is disassembled, the electrode is taken out and placed in a 40°C vacuum drying oven (vacuum degree: -0.01 MPa) for drying for 1 hour, the electrode is placed in a dry sealable glass bottle, 10 ml of deionized water is injected, and after fully stirring until there are no obvious bubbles in the glass bottle, filter and collect the remaining liquid. After fully stirring, 10 ml of gas is extracted from the glass bottle with a sealing needle, and it is passed into a gas chromatography device for testing to obtain a peak area of ​​H2 of 98.251, and the lithium element value in the solution is tested by an inductively coupled plasma spectrometer to be 403.62, and then brought into F( XA,XB )=Q1f1( XA )+Q2f2( XB ) was calculated and the result was about 2.00 mg, and the calculated lithium precipitation amount was about 0.65 mg.

[0052] Comparative Example 1: Only the relationship between lithium element and lithium content in aqueous solution is established (f2) XB), and then test it:

[0053] The obtained electrode was used to make a button half-cell with an average capacity of about 5.43 mAh after 3 weeks of 0.2C constant current charge and discharge cycle. It was discharged (lithium insertion) at 0.2C constant current to 120% SOC (about 6.52 mAh, the actual amount of lithium insertion was about 1.69 mg, and the "theoretical value" of lithium precipitation was about 0.28 mg) and left for 1 hour. The button battery was disassembled, the electrode was taken out and placed in a 40°C vacuum drying oven (vacuum degree: -0.01 MPa) for 1 hour, and the electrode was placed in a dry sealable glass bottle, 10 ml of deionized water was injected, and after fully stirring, there were no obvious bubbles in the glass bottle, and the remaining liquid was filtered and collected. The lithium element value in the solution was tested by an inductively coupled plasma spectrometer, which was 374.16. The function relationship accumulated in the early stage was used to calculate that x was about 1.80 mg, and the amount of lithium precipitation was about 0.39 mg.

[0054] Comparative Example 2: Only the relationship between lithium element and lithium content in aqueous solution is established (f2) XB ), and then test it:

[0055] The obtained electrode was used to make a button half-cell with an average capacity of about 5.09 mAh after 3 weeks of 0.2C constant current charge and discharge cycle. It was discharged (lithium insertion) at 0.2C constant current to 105% SOC (about 5.34 mAh, the actual amount of lithium insertion was about 1.38 mg, and the "theoretical value" of lithium precipitation was about 0.06 mg) and left for 1 hour. The button battery was disassembled, the electrode was taken out and placed in a 40℃ vacuum drying oven (vacuum degree: -0.01MPa) for 1 hour, and the electrode was put into a dry sealable glass bottle, 10 ml of deionized water was injected, and after fully stirring, there were no obvious bubbles in the glass bottle, and the remaining liquid was filtered and collected. The Li element value in the solution was tested by an inductively coupled plasma spectrometer, which was 340.07. The function relationship accumulated in the early stage was used to calculate that x was about 1.46 mg, and the amount of lithium precipitation was about 0.14 mg.

[0056] Comparative Example 3: Only the relationship between the hydrogen peak area and the lithium content is established. XA ), and then test it:

[0057] The obtained electrode was used to make a button half-cell with an average capacity of about 5.23mAh after 3 weeks of 0.2C constant current charge and discharge cycle. It was discharged (lithium insertion) at 0.2C constant current to 150% SOC (about 7.85mAh, the actual amount of lithium insertion was about 2.03mg, and the "theoretical value" of lithium precipitation was about 0.68mg) and left for 1h. The button cell was disassembled, the electrode was taken out and placed in a 40℃ vacuum drying oven (vacuum degree: -0.01MPa) for 1h, the electrode was put into a dry sealable glass bottle, 10ml of deionized water was injected, and after fully stirring, there was no obvious bubble in the glass bottle. After fully stirring, 10ml of gas was extracted from the glass bottle with a sealing needle, and it was passed into a gas chromatography device for testing to obtain a peak area of ​​H2 of 98.251. The function relationship accumulated in the previous period was used to calculate that x was about 1.94mg, and the amount of lithium precipitation was calculated to be about 0.59mg.

[0058] Comparative Example 4: Only the relationship between the hydrogen peak area and the lithium content is established. XA ), and then test it:

[0059] The obtained electrode was used to make a button half-cell with an average capacity of about 5.31 mAh after 3 weeks of 0.2C constant current charge and discharge cycle. It was discharged (lithium insertion) at 0.2C constant current to 110% SOC (about 5.84 mAh, the actual amount of lithium insertion was about 1.51 mg, and the "theoretical value" of lithium precipitation was about 0.13 mg) and left for 1 hour. The button battery was disassembled, the electrode was taken out and placed in a 40°C vacuum drying oven (vacuum degree: -0.01 MPa) for 1 hour, the electrode was put into a dry sealable glass bottle, 10 ml of deionized water was injected, and after fully stirring, there was no obvious bubble in the glass bottle. After fully stirring, 10 ml of gas was extracted from the glass bottle with a sealing needle, and it was passed into a gas chromatography device for testing to obtain a peak area of ​​H2 of 73.285. The function relationship accumulated in the previous period was used to calculate that x was about 1.47 mg, and the amount of lithium precipitation was calculated to be about 0.09 mg.

[0060] Absolute error: |theoretical value - test value|

[0061] Verification result analysis:

[0062] Table 1 Test results of the embodiments of the present invention and the comparative examples

[0063]

[0064] The method of the present invention can successfully test the total lithium content and lithium precipitation amount of the unknown battery negative electrode, and the absolute errors between the test values ​​and the theoretical values ​​obtained in Examples 1 to 4 are significantly lower than those in Comparative Examples 1 to 4.

[0065] It should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for testing the lithium content of a lithium-ion battery, characterized in that: The test method includes: S1: The lithium-ion battery to be tested is first charged and discharged in cycles; S2: Disassemble the lithium-ion battery, obtain the negative electrode plate and fully react with water, collect hydrogen and detect the lithium element in the aqueous solution, and bring the hydrogen content into the relationship between the hydrogen content and the lithium content f1( XA ), the content of lithium in the aqueous solution is brought into the relationship between lithium in the aqueous solution and lithium content f2 ( XB ); S3: Substitute the test results of hydrogen and lithium content into equation F( XA,XB )=Q1f1( XA )+Q2f2( XB ) to determine the lithium content in the negative electrode sheet, wherein Q1 is the relationship f1( XA ), Q2 is the weight of the relationship f2( XB ) weight, F( XA,XB ) is the relationship between the lithium content in the negative electrode sheet, and the weight Q1 and weight Q2 are obtained by the relationship f1( XA ) and the relation f2( XB ) is weighted by the square of the calibration error between the test value and the theoretical value.

2. The lithium content testing method of a lithium ion battery according to claim 1, characterized in that: The relationship between the hydrogen content and the lithium content is expressed as f1( XA ) comprises: selecting lithium metals of different masses and recording them as X1, X2, X3...Xn, placing lithium metals in a glass container, sealing the bottle mouth with a rubber stopper and a sealing cover, injecting deionized water, extracting gas, testing the content of hydrogen in the gas, recording them as XA1, XA2, XA3...XAn, fitting the mass X of lithium metal and the content of hydrogen to obtain the relationship between the content of hydrogen and the content of lithium f1( XA ).

3. The lithium content testing method of a lithium ion battery according to claim 2, characterized in that: The number of lithium metals is not less than 7; The mass of the lithium metal is 0.1 mg-1 g; The volume of the deionized water is 0.1 mL-1000 mL.

4. The lithium content testing method of a lithium ion battery according to claim 1, characterized in that: The relationship between the lithium element in the aqueous solution and the lithium precipitation is expressed as f2( XB ) comprises: selecting lithium metals of different masses and recording them as X1, X2, X3...Xn, placing the lithium metals in a glass container, sealing the bottle mouth with a rubber stopper and a sealing cover, injecting deionized water, filtering, testing the lithium element signal in the solution with an inductively coupled plasma spectrometer, recording them as XB1, XB2, XB3...XBn, fitting the mass X of the lithium metal and the content of the lithium element in the aqueous solution with a function, and obtaining a relationship between the lithium element in the aqueous solution and the lithium content f2( XB ).

5. The lithium content testing method of a lithium-ion battery according to claim 4, characterized in that: The number of lithium metals is not less than 7; The mass of the lithium metal is 0.1 mg-1 g; The volume of the deionized water is 0.1 mL-1000 mL.

6. The lithium content testing method of a lithium ion battery according to claim 1, characterized in that: The relationship between the hydrogen content and the lithium content is obtained as f1( XA ), we also need to correct the relation f1( XA ) for calibration, the calibration method comprising: selecting lithium metal with a mass of X, placing the lithium metal in a glass container, sealing the bottle mouth with a rubber stopper and a sealing cover, injecting deionized water, extracting gas, testing the hydrogen content XA in the gas, and substituting the test result XA into the relational formula f1( XA ) is calculated, and the result value is f1( XA ), by calibrating the theoretical value X with the test result value, the error value R1 is obtained.

7. The lithium content testing method of a lithium-ion battery according to claim 1, characterized in that: The relationship between lithium element and lithium content in aqueous solution is obtained as f2( XB ), we also need to correct the relationship f2( XB ) for calibration, the calibration method comprising: selecting lithium metal with a mass of X, placing the lithium metal in a glass container, sealing the bottle mouth with a rubber stopper and a sealing cover, injecting deionized water, filtering, and testing the lithium element signal in the solution with an inductively coupled plasma spectrometer. The test result is XB, and the test result XB is substituted into the relationship f2( XB ) is calculated, and the result is f2( XB ), by calibrating the theoretical value X with the test result value, the error value R2 is obtained; Further preferably, the Q1 is The Q2 is 8. The lithium content testing method of a lithium-ion battery according to claim 1, characterized in that: The charge-discharge cycle ratio is 0.01C-10C; the number of charge-discharge cycles is 1-100 times; After the charge and discharge cycle, the battery is charged until the SOC is 50%-200%; The area of ​​the negative electrode is controlled at 0.5 cm 2 -100cm 2 ; Before the negative electrode plate fully reacts with water, the negative electrode plate is dried, the drying temperature is 20°C-120°C, the drying time is 1h-24h, and the vacuum degree of the drying environment is -0.03MPa to -0.005MPa.

9. The lithium content testing method of a lithium-ion battery according to claim 1, characterized in that: The specific operation of disassembling the lithium-ion battery includes: disassembling the battery in an environment with a dew point controlled below -40°C, and fully placing the battery cell for 0.5h-1h before disassembling the battery cell; Further preferably, the negative electrode material of the lithium-ion battery is one of graphite, silicon-carbon material, silicon-oxygen material, and silicon material, and the positive electrode material is one of lithium nickel cobalt manganese oxide, lithium iron phosphate, lithium nickel cobalt aluminum oxide, lithium cobalt oxide, and lithium-rich manganese-based material.

10. Application of the lithium content testing method for lithium ion batteries according to any one of claims 1 to 9 in testing the lithium content and lithium deposition content of a negative electrode of a battery.

Citation Information

Cited By

  • Rapid quantitative detection method and system for lithium precipitation, storage medium and program product

    CN120121776A